Pelatihan Teknik Budidaya Ubikayu Nuabosi Menggunakan Teknologi Pola Tanam Tumpangsari Dengan Tanaman Legum Di Desa Randotonda Kecamatan Ende Kabupaten Ende - Willy Brordus Lanamana; Kristono Yohanes Fowo; Laurentius Dominicus Gadi Djou; Yohanes Pande (Universitas Andi Djemma, 2020)
AbstrakMitra dalam pelaksanaan kegiatan pengabdian ini adalah kelompok tani Kema Tau Pawe, yang dibentuk tahun 2010. Salah satu komoditas tanaman pangan yang dibudidayakan yaitu ubikayu varietas lokal Nuabosi. Ubikayu ini merupakan komoditas unggulan daerah. Permasalahan utama, teknik budidaya masih dilakukan secara konvensional, petani belum membuat guludan, tanpa pemupukan, jarak tanam yang tidak teratur, dan jarang melakukan pembersihan gulma, sehingga produktivitasnya rendah. Tujuan pelaksanaan pengabdian untuk melakukan perbaikan teknis budidaya menggunakan teknologi pola tanam tumpangsari ubikayu dan tanaman legum. Metode yang digunakan, penyuluhan dan pelatihan. Kegiatan pengabdian ini diawali dengan penyuluhan teknik budidaya. Materi pelatihan meliputi, teknik pembuatan guludan, pemanfaatan sereza dan pengaplikasian promi, pelatihan pola tanam tumpangsari serta pelatihan pembersihan gulma dan pembumbunan. Dari pretest dan posttest yang diberikan terjadi peningkat nilai yang signifikan pada posttest. Pada materi teknik pembuatan guludan rata-rata pretest 5,68, posttest meningkat sebesar 12,6, materi pemanfaatan sereza dan pemberian promi, rata-rata pretest 5,52, posttest meningkat sebesar 13,64, materi pola tanam tumpangsari rata-rata pretest 5,6, posttest meningkat sebesar 13,56 dan untuk materi pembumbunan dan pembersihan gulma, rata-rata pretest 5,52, posttest meningkat sebesar 14,2. Perbaikan teknis budidaya meliputi; pembuatan guludan, pemanfaatan sereza dan pengaplikasian promi, polatanam tumpangsari, pembersihan gulma dan pembumbunan. Kata Kunci: Tumpangsari Legum, Ubikayu Nuabosi AbstractPartner in the implementation of community service activity was Kema Tau Pawe farmer group, which was formed in 2010. One of the food crop commodities cultivated by this farmer group was Nuabosi cassava, in which this cassava was their regional superior commodity. The main problem of Nuabosi cassava cultivation was that the cultivation technique was still performed conventionally, in which farmers did not make mounds, did not perform fertilization, planted the plants in irregular spacing, and rarely performed weed control, so that it led to the low productivity. The specific objective of the implementation of this service activity was to carry out technical improvements in Nuabosi cassava cultivation using the Nuabosi cassava intercropping system with legumes. Methods used were counseling and training methods. The community service activity was begun with counseling about cultivation techniques. There were four materials provided in training, such as techniques for making mounds, the use of cereals and application of promi, training in intercropping system and training for weed control and embellishments. Based on pretest and posttest given to famer group for the four materials, it was found that there was significant increase in the posttest score. First, in the material containing techniques for making mounds, the average of pretest score was 5.68, and it increased in the posttest, which was 12.6. Next, in the material about the use of cereals and application of promi, the average of pretest score was 5.52, and it increased in the posttest, which was 13.64. Then, in the material about intercropping system the average of pretest score was 5.6, and it increased in the posttest, which was 13,56. The last, in the material about weed control and embellishments, the average of pretest score was 5.52, and it increased in the posttest, which was 14.2. Technical improvements for cultivation include; making mounds, the use of cereals and application of promi, intercropping, weed control and embellishments. Keywords: Intercropping Legumes, Nuabosi Cassava